“Nurabulla Zhyrau School and its Descendants in Karakaplak Zhyrau Art” - Ayapov Salamat Bakhievich (Zien Journals, 2022)
Nurabulla’s zhyrau performance, deepness of the voice is considered to be one of the most famous one in Karakalpak national zhyrau art. He was the one who contributed into the development and spreading of the zhyrau and was loved by the people.
Keywords: zhyrau; gobiz; zhyrau school; “dastan”